(4x-1)=(2x+5)

Simple and best practice solution for (4x-1)=(2x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4x-1)=(2x+5) equation:


Simplifying
(4x + -1) = (2x + 5)

Reorder the terms:
(-1 + 4x) = (2x + 5)

Remove parenthesis around (-1 + 4x)
-1 + 4x = (2x + 5)

Reorder the terms:
-1 + 4x = (5 + 2x)

Remove parenthesis around (5 + 2x)
-1 + 4x = 5 + 2x

Solving
-1 + 4x = 5 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-1 + 4x + -2x = 5 + 2x + -2x

Combine like terms: 4x + -2x = 2x
-1 + 2x = 5 + 2x + -2x

Combine like terms: 2x + -2x = 0
-1 + 2x = 5 + 0
-1 + 2x = 5

Add '1' to each side of the equation.
-1 + 1 + 2x = 5 + 1

Combine like terms: -1 + 1 = 0
0 + 2x = 5 + 1
2x = 5 + 1

Combine like terms: 5 + 1 = 6
2x = 6

Divide each side by '2'.
x = 3

Simplifying
x = 3

See similar equations:

| 30+5=51 | | -25x-6=-5(5x+7)+29 | | 10x+2+4x=(2+12)x-3+5 | | .25a-2=5 | | 12x-3(3x-6)=18+3x | | x-x(.25)=42000 | | 11(w+2)+14=2 | | 15b-2b=-9 | | 6x-30=7-2x | | 2x+3+6x-1=8x+2 | | -2(4+m)=10 | | 2x+3+6X-1=x+2 | | 27j-6=14j-7 | | 112=7w-168 | | 30m=22+80m | | 2x+24=-30+5x | | 21x+7=10x-1 | | 5(g-6)=48 | | 1.5x=1.23 | | r-9-(-42)=96 | | 9+4+10=56 | | 8(3x+40)=10 | | x^2-320=x-10 | | 3overx= | | 15=k-32 | | 3x+2-2=8-2 | | 18p-15=0 | | T(-3)=21 | | 2X+1=-x+2 | | -x+(-x)+(-x)+(-z)= | | 1.6k=5.75 | | 2x+12=3x-9 |

Equations solver categories